The dream snake - Howard, Robert E. (Robert Ervin), 1906-1936 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Dream Snake" by Robert E. Howard is a short story published in the late 1920s. This eerie tale features elements of horror and psychological suspense, exploring the realm of nightmares and the fear of the unknown. The story delves into the psychological experiences of the protagonist as he recounts an extremely vivid and haunting recurring dream that blurs the line between reality and imagination. In the narrative, a man named Faming shares a horrifying dream about living in a solitary bungalow on a hill in Africa, where he feels a constant dread of being pursued by a monstrous serpent. As he describes the dream, Faming experiences intense fear and an overwhelming sense of impending doom, especially as he senses the serpent drawing nearer with each repetition of the dream. The story paints a vivid picture of his terror as he waits in the bungalow, grappling with his sanity while paralyzed by the anticipation of the serpent's arrival. Ultimately, the tale reaches a chilling conclusion with Faming's untimely death, suggesting the devastating power of fear and the psychological impact of one's nightmares becoming a horrifying reality. (This is an automatically generated summary.)
Release date is 2023-06-26
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Short stories; Horror tales; Nightmares -- Fiction